The Effect of Product Quality and Service Quality on Tourist Satisfaction and Revisit Intention to La Brisa Bali - Ni Luh Putu Erisca Putri; I Wayan Suardana; Ni Ketut Arismayanti (International Journal of Economics, Business and Innovation Research, 2024)
La Brisa Bali is a renowned beach club located in the tourist hub of Canggu, Bali. The name "La Brisa" reflects the untamed yet captivating and soothing nature of the sea breeze. This study purposes to analyzing the effect of service quality and product quality on tourist satisfaction and their intention to revisit La Brisa Bali. A quantitative approach was employed, with a sample of 200 respondents selected through purposive sampling. Data collection methods included questionnaires, interviews, observations, and literature review. Data analysis was conducted using Structural Equation Modelling (SEM) with SmartPLS 3.3.3. The results indicate that service quality and product quality both significantly and positively affect tourist satisfaction. Tourist satisfaction, in turn, positively influences their intention to revisit. Furthermore, service quality and product quality directly and indirectly affect the intention to revisit, mediated by tourist satisfaction.